Prioritizing issues in Islamic economics and finance - Abduh, Muhamad (IDOSI Publications, 2013)
The purpose of this study is to investigate the opinion of scholars of Islamic economics and finance upon which issues should be given higher priority based on its roles in achieving the ultimate goals of Islamic economics and finance. Library study is firstly used to determine research areas in Islamic economics and finance. Afterwards, the pairwise comparison matrix is developed and distributed among the Islamic economics and finance scholars in Malaysia. Analytic hierarchical process technique is used as the means to rank the importance of alternatives based on defined research areas and small sample size. The library study found that there are six major research areas in Islamic economic and finance i.e. Islamic banking, other Islamic financial institutions, zakat-waqaf and poverty alleviation, Islamic monetary system, philosophical issues and fiqh almuamalat al-maliyyah. Using Analytical Hierarchy Process, the result shows that area of zakat-waqaf and poverty alleviation is considered as the most important area followed by monetary system including Islamic currency. Despite the large number of studies done in Islamic banking, the respondents have considered that the area is not able to answer or give solution to the ultimate goal of the establishment of Islamic economic and finance.